Characteristics of AC. Conductivity and Dielectric Behavior of Cu0.5 Ti0.5 Hox Fe2-x O4 Ferrites - Al-Hilli, Muthafar F. (Iraqi Journal of Science, 2022)
Ferrites with the formula Cu0.5Ti0.5HoxFe2-xO4 (x= 0 and 0.09) were prepared by standard ceramic method. The powder mixtures were presintered at 900 oC for 5h. The final sintering of the pellets was performed at 1100 oC for 2 hrs. The dielectric properties and AC conductivity were measured at different temperatures over the frequency range 100Hz - 10MHz. The variation in dielectric constant with frequency revealed that dispersion is due to the Maxwell–Wagner type of interfacial polarization in accordance with Koop’s phenomenological theory. This ferrite showed high value of dielectric constant. At low frequencies the dielectric constant and dielectric loss factor was found to decrease with the increase in frequency and Ho addition. The dielectric loss decreased with temperature rise. The frequency dependence of dielectric loss tangent is found to be abnormal at various temperatures, the abnormal behavior of dielectric relaxation processes was observed. The prepared ferrite showed low range of AC conductivity. The AC conductivity was noticed to increase with frequency and temperature. While the conductivity decreased with Ho addition.